2015
DOI: 10.1111/crj.12393
|View full text |Cite
|
Sign up to set email alerts
|

Brain‐volume changes in young and middle‐aged smokers: a DARTEL‐based voxel‐based morphometry study

Abstract: Young and middle-aged male smokers had many smaller brain areas than non-smokers. Some of these areas' volume had negative correlation with pack-years, while some had not. These may due to different pathophysiological role of smokings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 55 publications
1
14
0
Order By: Relevance
“…The observed volumetric decrease in the thalamus of cigarette smokers is in congruence with several prior studies (Gallinat et al, 2006; Almeida et al, 2008; Liao et al, 2012; Peng et al, 2017). Recently, Sutherland et al (2016) performed a coordinate-based meta-analysis of MRI studies related to chronic smoking, which suggest that thalamus is one of the structures showing consistent structural decreased in smokers.…”
Section: Discussionsupporting
confidence: 92%
“…The observed volumetric decrease in the thalamus of cigarette smokers is in congruence with several prior studies (Gallinat et al, 2006; Almeida et al, 2008; Liao et al, 2012; Peng et al, 2017). Recently, Sutherland et al (2016) performed a coordinate-based meta-analysis of MRI studies related to chronic smoking, which suggest that thalamus is one of the structures showing consistent structural decreased in smokers.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have found that smokers exhibit structural changes in some brain areas in comparison to non-smokers ( Karama et al, 2015 ; Peng et al, 2015 ; Prom-Wormley et al, 2015 ). Our previous study went further to discover that brain tissue atrophy becomes more obvious with the associated smoking amount (pack-years) ( Peng et al, 2015 ), which demonstrates that pack-years is an effective indicator of smoking-related structural damages in the brain. In this study, we found that severe nicotine dependence smokers demonstrated less brain atrophy than moderate nicotine dependence smokers, interestingly illustrating a distinct change trend in comparison to the findings from pack-years.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking account and nicotine dependence are two independent factors on smokers, It is well accepted that more smoking account could cumulatively lead to more serious brain alternations, and our previous study had reported the structural changes in the brain related to the lifetime tobacco consumption (in pack-years) ( Peng et al, 2015 ). However, whether nicotine dependence also displays such a trend as smoking account is still unknown for smokers, and we speculate nicotine dependence may have distinct effects on the brain compared to the smoking account.…”
Section: Introductionmentioning
confidence: 99%
“…Structural imaging studies have largely shown that problematic use of substances, such as cocaine (Rando, Tuit, Hannestad, Guarnaccia, & Sinha, 2013), opioids (Wollman et al, 2017), alcohol (Heikkinen et al, 2017), and cigarettes (Peng et al, 2017), is associated with reduced gray matter volumes in the insular cortex, typically bilaterally. In many cases, these structural differences are especially pronounced in the posterior parts of the insula (Droutman et al, 2015).…”
mentioning
confidence: 99%